Magnetic, thermal, and optical properties of single-crystalline CoTa2O6 and FeTa2O6 and their anisotropic magnetocaloric effect. (17th April 2018) - Christian, A B; Schye, A T; White, K O; Neumeier, J J
Abstract: The magnetic, thermal, and optical properties of single-crystalline CoTa2 O6 and FeTa2 O6 are reported. Optical dichroism was observed in CoTa2 O6 . Magnetic susceptibility χ ( T ) measurements reveal long-range antiferromagnetic order with Néel temperatures K and 8.11(5) K, respectively, and anisotropy in χ . The thermal expansion coefficients exhibit significant anisotropy and the influence of the magnetic ions and long-range order. A structural phase transition to orthorhombic occurs below T N for FeTa2 O6 . Magnetic field H lowers T N with its affect largest when H is directed along either [1 1 0] or [1 0], and smallest when directed along [0 0 1]. This leads to an anisotropic magnetocaloric effect that is investigated through measurements of the specific heat and magnetization in applied magnetic field.